Peyronie's disease in a patient after COVID‐19 infection: A case report. (16th August 2021) - Rainer, Quinn; Molina, Manuel; Ibrahim, Emad; Saltzman, Russell; Masterson, Thomas; Ramasamy, Ranjith
Abstract: Coronavirus disease 2019 (COVID‐19) is an emerging infectious disease caused by a novel coronavirus (SARS‐CoV‐2), which demonstrates the ability to invade endothelial cells and cause systemic inflammation. Many possible long‐term sequelae of COVID‐19 remain unidentified. We describe a case of a man who developed Peyronie's disease after a resolved COVID‐19 infection. Erectile dysfunction was confirmed by the International Index of Erectile Function‐15(IIEF) and Sexual Health Inventory for Men(SHIM) scores. A diagnosis was Peyronie's disease was confirmed on ultrasound. Furthermore, he was found to have low endothelial progenitor cells colony‐forming units and low brachial artery flow‐mediated vasodilation, both of that are indicative of endothelial dysfunction. This case suggests Peyronie's disease should be considered as a possible sequela of COVID‐19 infection and providers should inquire about a history of COVID‐19 infection in patients presenting with Peyronie's disease.